Kenya Country Economic Memorandum : From Economic Growth to Jobs and Shared Prosperity - World Bank Group (World Bank, Washington, DC, 2016)
The Kenya CEM has five main messages. First, Kenya has performed well in the past decade in terms of economic growth, and modern services are behind the acceleration of growth. Expansion in these services, such as financial intermediation and mobile communications have stimulated demand for other services such as trade. The CEM discusses how to maximize the potential of services, especially given that most formal, high quality jobs are created in this sector. Second, agriculture, which still contributes to over a quarter of the economy, and manufacturing have stagnated. The CEM discusses the reasons behind this stagnation, noting that agriculture and manufacturing have not been able to create enough jobs for Kenya's growing working age population. Most of the jobs are created by the informal economy and are concentrated in low productivity segments of trade, hospitality, and jua kali. Improving the ease of doing business is one way towards job creation and higher productivity. However there is still a need for creating job opportunities for the rural poor, for poverty reduction and achieving shared prosperity. Reviving agriculture, in particular, remains the pathway for poverty reduction. Third, accelerating growth to meet Kenya's development goals requires technological advances and innovation that raise firms' productivity. Fourth, achieving rapid growth will require macroeconomic stability to boost investment and savings. And as the government strives to build Kenya's energy and transport infrastructure, this needs to be complemented with improvements in the public investment management process and better execution. Fifth, the discovery of oil opens a possibility for raising Kenya's growth. Kenya's recent oil discoveries, if used prudently, can contribute to achieving the Vision 2030 goals. The World Bank Group is proud of its long-standing relationship with Kenya, and looks forward to continuous collaboration with both National and County Governments and other partners. Working together, Kenya can realize its potential to lift millions of families out of poverty and achieve shared prosperity.